Coincidence of Glanzmann's thrombasthenia with hereditary haemorrhagic telengiectasia in a man with gastrointestinal bleeding. Issue 1 (January 2015) - Khosravi, Ahmad; Rahimi, Hossein; Mansouritorghabeh, Hassan
<x xml:space="preserve">Abstract</x> Here we report a case of a 57-year-old man referred to our hospital with weakness, lethargy, melena, and rectorrhalgia. His physical examination and past medical history showed gingival bleeding, several episodes of epistaxis and post-surgery bleeding. Primary laboratory evaluation revealed only anaemia. Gastrointestinal findings including upper endoscopy and colonoscopy documented normal status, but balloon endoscopy illustrated telengiectasia-like lesions in the mid-jejunum. The case was suspected to be haemophilia due to the past medical history, although complete haemostatic evaluation demonstrated Glanzmann's thrombasthenia. The diagnosis of co-occurrence of hereditary haemorrhagic telengiectasia and Glanzmann's thrombasthenia was confirmed. This case revealed the coincidence of two bleeding tendencies, which, although rare, is a possible phenomenon. We recommend carrying out both primary and secondary haemostatic profiles for every patient with bleeding diathesis.